Systematic Review of the Relationship between Acute and Late Gastrointestinal Toxicity after Radiotherapy for Prostate Cancer - Matthew Sean Peach; Timothy N. Showalter; Nitin Ohri (Prostate Cancer)
A small but meaningful percentage of men who are treated with external beam radiation therapy for prostate cancer will develop late gastrointestinal toxicity. While numerous strategies to prevent gastrointestinal injury have been studied, clinical trials concentrating on late toxicity have been difficult to carry out. Identification of subjects at high risk for late gastrointestinal injury could allow toxicity prevention trials to be performed using reasonable sample sizes. Acute radiation therapy toxicity has been shown to predict late toxicity in several organ systems. Late toxicities may occur as a consequential effect of acute injury. In this systematic review of published reports, we found that late gastrointestinal toxicity following prostate radiotherapy seems to be statistically and potentially causally related to acute gastrointestinal morbidity as a consequential effect. We submit that acute gastrointestinal toxicity may be used to identify at-risk patients who may benefit from additional attention for medical interventions and close follow-up to prevent late toxicity. Acute gastrointestinal toxicity could also be explored as a surrogate endpoint for late effects in prospective trials.